What is the best fitting function? Evaluation of lactate curves with common methods from the literature - Endler, S.; Secker, C.; Bügner, J. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
Using the lactate threshold for training prescription is the gold-standard, although there are several open questions. One open question is: What is the best fitting method for the load-lactate data points? This investigation re-analyses over 3500 lactate diagnostic datasets in swimming. Our evaluation software examines six different fitting methods with two different minimization criteria (RMSE and SE). Optimization of parameters of the functions is put in excecution with gradient descent. Prom a mathematical point of view, the double phase model, which consists of two linear regression lines, shows the least errors (RMSEmin 0.254 ± 0.172; SEmin 0.311 ± 0.210). However, this method cannot be used for every further determination of lactate thresholds. Some threshold determination models need a single curve. In these cases, the exponential function shows the least errors (RMSEmin 0.846 ± 0.488; SEmin 1.196 ± 0.689). This confirms the default fitting method used in practice.